Conclusion: Historical Perspectives on Borderlands, Boundaries and Migration Control*. Issue 4 (8th August 2019) - Fahrmeir, Andreas
ABSTRACT: This conclusion relates the articles in this special issue—which focus on European migration control regimes from the 19 th century to the present—to two recent trends in the historiography of migration regulation: the impact of research on the early modern period and of global perspectives. Both can lead to a conceptualization of borderlands beyond zones surrounding a frontier, which may lead to additional research questions.